Compounds and their uses

By combining poly(vinyl alcohol) (PVOH), crosslinking compounds and bioplastics, a composite with a predetermined life is prepared, which solves the problem that existing polymer materials are difficult to achieve biodegradation and functionality, and realizes the material It has both degradability and functionality and reduces environmental impact.

CN114269842BActive Publication Date: 2024-12-17SOLUTUM TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080057196.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-12
Filing Date
2020-08-12
Publication Date
2024-12-17
Estimated Expiration
2040-08-12

AI Technical Summary

Technical Problem

Existing polymer materials are difficult to achieve biodegradability and function at the same time, and their environmental impact is great, resulting in difficult processing.

Method used

By combining poly(vinyl alcohol) (PVOH), crosslinking compounds and bioplastics, the mechanical properties and degradation properties of the material are adjusted to prepare a composite with a predetermined lifespan that can decompose upon water contact and produce low toxic degradation products.

Benefits of technology

The biodegradability and functionality of polymer materials are achieved, which reduces environmental impacts, and customizes products with specific mechanical properties and degradation rates by adjusting the material composition and processing conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003502175150000101
    Figure BDA0003502175150000101
  • Figure BDA0003502175150000111
    Figure BDA0003502175150000111
  • Figure BDA0003502175150000112
    Figure BDA0003502175150000112
Patent Text Reader

Abstract

The technology disclosed herein relates to a method for modifying the properties of raw materials, providing a final composite with preselected and unique mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to methods for making polymeric composites and uses thereof. Background Art

[0002] Polymers and products made therefrom form a significant portion of municipal solid waste. These materials are virtually non-biodegradable and some of them are difficult to recycle. Although manufacturers generally desire to produce biodegradable materials that will contribute to sustainability and reduce the environmental impact associated with the disposal of such polymers, extremely large quantities of polluting polymers are still manufactured and disposed of.

[0003] Over the years, researchers have attempted to produce polymer compositions that are not only functional, i.e., have certain desirable properties, but are also safe and have limited or reduced environmental impact. These attempts are described, for example, in any of the following references [1] to

[24] . Background Art

[0005] [1] International Patent Publication No. WO07 / 010553;

[0006] [2] International Patent Publication No. WO13 / 029018;

[0007] [3] Japanese Patent Application No. 2009091011;

[0008] [4] International Patent Publication No. WO17 / 214187;

[0009] [5] International Patent Publication No. WO13 / 044266;

[0010] [6] Japanese Patent Application No. 4265200;

[0011] [7] International Patent Publication No. WO04 / 037919;

[0012] [8] International Patent Publication No. WO16 / 083667;

[0013] [9] International Patent Publication No. WO14 / 003369;

[0014]

[10] International Patent Publication No. WO11 / 098122;

[0015]

[11] International Patent Publication No. WO06 / 117801;

[0016]

[12] International Patent Publication No. WO06 / 082471;

[0017]

[13] International Patent Publication No. WO02 / 053640;

[0018]

[14] International Patent Publication No. WO02 / 053610;

[0019]

[15] International Patent Publication No. WO07 / 049952;

[0020]

[16] International Patent Publication No. WO15 / 142564;

[0021]

[17] International Patent Publication No. WO03 / 082970;

[0022]

[18] International Patent Publication No. WO91 / 02023;

[0023]

[19] International Patent Publication No. WO15 / 145457;

[0024]

[20] International Patent Publication No. WO17 / 112878;

[0025]

[21] International Patent Publication No. WO95 / 20013;

[0026]

[22] International Patent Publication No. WO04 / 074367;

[0027]

[23] International Patent Publication No. WO07 / 015261;

[0028]

[24] U.S. Patent No. 7,993,738.

[0029] General Description

[0030] The inventors of the technology disclosed herein have developed a new method for modifying the properties of raw materials in order to replace plastics and other long-degrading polymers with new materials that can be pre-customized to decompose. The composites of the present invention provide a range of final products, all of which are constructed based on the selection of materials, which, when combined according to the present invention, provide a final composite with pre-selected and unique mechanical properties. The ability to customize a composite or product with a predetermined lifespan, that is, the ability to determine how quickly a composite or product will degrade at the time of production, is an essential feature of the technology disclosed herein. By selecting a set of appropriate manufacturing parameters, including material composition, material quantity, processing conditions, etc., products with a predetermined lifespan can be customized. Such products will decompose, for example, when in contact with water, or will naturally degrade after a predetermined period of time, leaving behind less toxic degradation products that can sometimes be easily absorbed by naturally occurring microorganisms.

[0031] In the most general sense, the present invention provides a composite (i.e., raw material or product) comprising a collection of polymeric materials and non-polymeric materials, the combination or amount of which imparts a variety of properties to the composite. The properties can be further customized by adjusting the amount of any of the PVOH, cross-linked moieties, and bioplastics. Such properties include OTR and / or gas permeability, water solubility (or water degradation), thermal stability, heat sealing, and mechanical properties such as tensile strength, Young's modulus, maximum elongation, flexibility, rigidity, shrinkage or stretching characteristics, and others.

[0032] As disclosed herein, the composition according to the present invention is a set of ingredients as disclosed, which is in the form of (composition and amount) suitable for undergoing chemical treatment to provide a solid composite. Although the composite is based on and comprises the components of the composition derived therefrom, in the composite, some components may be in the form of reaction or crosslinking. The composite of the present invention can be provided as a raw material, as a masterbatch, in the form of partial processing or in the form of a final product. Non-limiting examples of composite forms include masterbatch, granular raw materials, powdered raw materials, fibers, sheets of any thickness, polymer blocks and any final product form.

[0033] Therefore, in its first object, the present invention provides a composition comprising:

[0034] A-poly(vinyl alcohol) (PVOH);

[0035] B - at least one cross-linking compound (e.g., selected from polymers, copolymers, and non-polymeric materials as described herein);

[0036] C - at least one additional bioplastic; and

[0037] D - Optionally at least one additive.

[0038] In some embodiments, the compositions of the present invention comprise:

[0039] A - poly(vinyl alcohol) (PVOH) in an amount ranging between 30 wt% and 99 wt%;

[0040] B - at least one cross-linking compound present in an amount ranging between 0.1 wt% and 20 wt%;

[0041] C - at least one additional bioplastic in an amount ranging between 0.1 wt% and 50 wt%; and

[0042] D - Optionally, at least one additive in an amount ranging between 0.1 wt% and 20 wt%.

[0043] Poly(vinyl alcohol) (PVOH) is a highly hydrophilic water-soluble polymer. The degree of hydroxylation determines its physical, chemical and mechanical properties, wherein the fewer the number of residual acetate groups, the lower its water solubility and the higher its glass transition temperature. The degree of hydroxylation also affects the maximum water absorption, which acts as a plasticizer and thereby affects the mechanical and physical properties of the polymer. With increasing water absorption, tensile strength, elastic modulus and hardness decrease, while impact resistance and elongation at break greatly increase. Any form of PVOH is encompassed in the invention disclosed herein.

[0044] Films made from PVOH have good heat sealing properties, excellent barrier properties to gases such as oxygen and carbon dioxide, and are biocompatible, biodegradable and non-toxic. However, the films are highly hydrophilic and highly susceptible to water-derived decomposition, which makes them essentially impractical. In order to impart the desired mechanical properties to PVOH while controlling the decomposition rate when exposed to water, the composition of the present invention also comprises one or more additives or materials in a specified amount or at a specified material ratio that changes the properties of PVOH and imparts one or more desired properties to the composition or a composite made therefrom.

[0045] In some embodiments, at least one cross-linking compound is a compound capable of associating or cross-linking with PVOH. As indicated, the cross-linking compound is selected from polymers, copolymers, and non-polymeric materials, each of which has a functional group capable of associating with the PVOH backbone or any functional group present thereon.

[0046] In some embodiments, at least one cross-linking compound is a polymer or oligomer capable of cross-linking or associating with PVOH. The cross-linking or association with PVOH is usually chemical in nature, i.e., by forming covalent bonds. In other cases, the association can be physical, i.e., where the chains of the polymers are entangled. Regardless of the type of association, the cross-linking molecule is selected to provide an association that results in the desired physical-mechanical properties.

[0047] The crosslinking compound is a crosslinking compound having a functional group capable of associating with PVOH. Such a functional group may be an inherent functional group of the polymer or a functional group grafted or associated or attached to the polymer to provide crosslinking capability. In some embodiments, the functional group is selected from alcohols, epoxides, anhydrides, carboxylic acids, amines, amides, glycidyl functional groups, aldehyde functional groups, esters, and others.

[0048] The polymer may be selected from ionomers, ie polymers having functional groups capable of forming ionic groups. In some embodiments, the ionomer is a polyacid, optionally selected from poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA), and others.

[0049] In some embodiments, the crosslinking compound is a polymer grafted with an anhydride such as maleic anhydride. In some embodiments, the polymer onto which maleic anhydride is grafted is selected from polyethylene (PE), poly(lactic acid) (PLA), polycaprolactone (PCL), polyhydroxybutyrate (PHB), poly(butylene adipate-co-terephthalate) (PBAT) and others. In some embodiments, the crosslinking compound is polyethylene-graft-maleic anhydride.

[0050] In some embodiments, the crosslinking compound is a polymer with carboxylic acid functional groups. In some embodiments, the polymer is selected from poly (ethylene-co-acrylic acid) (PE-co-AA), poly (ethylene-co-methacrylic acid) (PE-co-MAA), poly (lactide-block-acrylic acid) (PLA-block-AA), PVOH with carboxyl groups, carboxymethyl cellulose (CMC) and others.

[0051] In some embodiments, the polymer is poly(ethylene-co-acrylic acid).

[0052] In some embodiments, the polymer is a polymer having glycidyl functional groups.

[0053] In some embodiments, at least one cross-linking compound is a copolymer.

[0054] In some embodiments, the cross-linking compound is a low molecular weight cross-linking compound that is not a polymer, oligomer or copolymer. The compound is typically selected from aldehyde compounds, such as compounds having one or more aldehyde functional groups; carboxylic acid compounds, such as compounds having one or more carboxylic acid functional groups, and others.

[0055] In some embodiments, the aldehyde compound can be selected from monoaldehydes and dialdehydes. In some embodiments, the aldehyde is selected from formaldehyde, glutaraldehyde, glyoxal, malondialdehyde, succinaldehyde, o-phthalaldehyde, and others.

[0056] In some embodiments, the carboxylic acid compound is selected from monocarboxylic acids, dicarboxylic acids, tricarboxylic acids and higher homologues. These carboxylic acids can be selected based on the number of carboxylic acid esters or basic groups that they can form. Therefore, in the same way, these compounds can be selected from monoprotic acids, diprotic acids, triprotic acids and higher homologues. In some embodiments, the carboxylic acid compound is selected from citric acid, boric acid, humic acid, phthalic acid, terephthalic acid, malic acid, sulfosuccinic acid, isophthalic acid, aconitic acid and others.

[0057] The additional bioplastics (or simply "bioplastics") used according to the present invention are polymers that are different from the other polymer components used in the composition, all other polymer components being also substantially bioplastics. The additional bioplastics may be represented by natural polymers that are produced or derived from natural sources such as cells of living organisms, plants and other natural sources. Such polymers may be completely natural or partially synthetic, i.e. derived from nature and chemically modified to structurally modify the natural polymers. The bioplastics used according to the present invention may also be represented by biodegradable or compostable polymers that are derived in part or in whole from petrochemical resources.

[0058] In some embodiments, the additional bioplastic is selected from polypeptides and polysaccharides.

[0059] In some embodiments, the additional bioplastic is selected from aliphatic or aromatic polyesters, copolyesters or polyesteramides.

[0060] In some embodiments, the additional bioplastic is selected from poly(ethylene oxide) (PEO), poly(ethylene glycol) (PEG), polycaprolactone (PCL), poly(lactic acid) (PLA), cellulose and cellulose derivatives, starch, thermoplastic starch (TPS), chitosan, polyhydroxyalkanoates (PHA), such as polyhydroxybutyrate (PHB).

[0061] Cellulose derivatives are crystalline derivatives thereof or any other amorphous form of such materials. Non-limiting examples include nanocrystalline cellulose (NCC), microfibrillar cellulose, bacterial cellulose, hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC) and carboxymethyl cellulose (CMC).

[0062] In some embodiments, the additional bioplastic is PEO.

[0063] In some embodiments, the additional bioplastic is PCL.

[0064] In some embodiments, the additional bioplastic is PEG.

[0065] In some embodiments, the composition comprises both PEO and PCL.

[0066] In some embodiments, the composition comprises PVOH, PAA, PEO, and optionally PCL.

[0067] At least one additive used in the composition of the present invention can be selected from inorganic additives, fillers or reinforcing agents, and from low molecular weight additives (having a molecular weight of less than 1000 Da) for improving various properties, such as processing aids, slip agents, light stabilizers, UV absorbers, flame retardants, antimicrobial agents, antiviral agents, foaming agents, nucleating agents, antioxidants, anti-caking agents, antistatic agents and others.

[0068] In some embodiments, the additive is a hygroscopic agent. Such an agent can be selected from CaO, CaCl2, LiCl, NaCl, CaI2, MgCl2, TiO2, CaCO3, aluminum silicate fillers, SiO2 and others. In some embodiments, the additive is CaO.

[0069] In some embodiments, the additive is an inorganic salt comprising a metallic element or a non-metallic element. In some embodiments, the inorganic salt is an inorganic salt of a metal selected from alkali metals and alkaline earth metals. In some embodiments, the inorganic salt is a salt of a transition metal. The non-limiting examples of inorganic salts include halide salts selected from Li, K, Ca, Na, Mg, Mn, Zn and other metals. The inorganic salt is typically a halide salt (halide atom is an anion of a metal cation). In some embodiments, the inorganic salt is selected from LiCl, NaCl, CaCl2, CaI2 and MgCl2. In some embodiments, the inorganic salt is CaCl2.

[0070] In some embodiments, the composition used according to the present invention includes poly(vinyl alcohol) (PVOH), poly(ethylene oxide) (PEO) and poly(acrylic acid) (PAA). The composition can be treated to include one or more additional components selected primarily from inorganic salts, cellulose-derived materials and chitosan.

[0071] The inorganic salt used to improve the properties of the solid composite of the present invention can be any salt form of a metallic element or a non-metallic element. In some embodiments, the inorganic salt is an inorganic salt of a metal selected from alkali metals and alkaline earth metals. In some embodiments, the inorganic salt is a salt of a transition metal. Non-limiting examples of inorganic salts include halide salts selected from Li, K, Ca, Na, Mg, Mn, Zn and other metals. The inorganic salt is typically a halide salt (the halide atom is the anion of the metal cation). In some embodiments, the inorganic salt is selected from LiCl, NaCl, CaCl2, CaI2 and MgCl2. In some embodiments, the inorganic salt is CaCl2.

[0072] A cellulose-derived substance is any such material comprising or based on cellulose or a cellulose derivative. In some embodiments, the cellulose-derived substance is cellulose or a crystalline structure thereof, such as nanocrystalline cellulose (NCC), microfibril cellulose, and bacterial cellulose. In some embodiments, the cellulose-derived material is selected from hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC), and carboxymethyl cellulose (CMC).

[0073] By selecting a material composition from the material families disclosed herein, at least one property of a solid polymer material can be adjusted during its manufacturing process. The properties that can be adjusted are mechanical properties, chemical properties or physical properties selected from water degradation, gas permeability, rigidity, flexibility and elasticity. More specifically, the properties that can be adjusted can be considered as water solubility or water degradation, oxygen transmission rate (OTR) and / or gas transmission rate, thermal stability, heat sealing and mechanical properties such as tensile strength, Young's modulus, maximum elongation, flexibility, rigidity, shrinkage or stretching properties and others.

[0074] The oxygen transmission rate (OTR) is a measure of the amount of oxygen that passes through the solid composite according to the invention at the measured temperature in a given period of time. When the amount of PVOH is increased, the permeation of gases other than oxygen can also be prevented. Such other gases can be, for example, carbon dioxide.

[0075] In some embodiments, the amount of PVOH, the amount of at least one cross-linking compound, and the amount of at least one additional bioplastic are selected to modulate water degradation of a composite formed from the composition.

[0076] As stated above, the ability to customize composites with a predetermined lifespan, i.e., the ability to determine how quickly they degrade, or, in different terms, how long they can remain in contact with moisture or dampness before they degrade, is a fundamental feature of the technology disclosed herein. The composites of the present invention can be made more or less sensitive to hydrolysis (hydro-decomposition) by controlling the amount of cross-linked materials and / or other bioplastics used, such as PAA and / or PEO or cellulose-derived materials. As used herein, "water degradation" means that a solid composite prepared from the composition of the present invention partially or completely dissociates when the composite is in contact with water. In some cases, the composites of the present invention can be stable to hydrodegradation (hydro-degradation) for a period of time, but will begin to deteriorate after the period of time has passed. This is considered as product life in this article. Other products will only be easily degraded in water if they are in contact with water for a certain period of time. Such a product can be considered to have a chemical self-destruct switch that can be triggered by exposing the composite to water.

[0077] Water degradation can cause the complex to dissociate into fragments that can be easily decomposed and further water-degraded or chemically digested by natural microorganisms. According to the present invention, stability to water can be tested, verified or determined based on any such assay known in the art. In some embodiments, one or more of the following can be used:

[0078] 1- Determine the time or rate of decomposition to complete dissolution when stirred in water at room temperature;

[0079] 2- Determine the time or rate of decomposition to complete dissolution when stirred in water at a temperature above room temperature; or

[0080] 3-Biodegradation test.

[0081] For example, the water degradation rate of the composites of the present invention was determined as the time required for the composite to dissolve or degrade under accelerated conditions and with stirring at ambient temperature at all times in a water tank, i.e., under conditions where the concentration of the composite dissolved in water is negligible compared to the amount of water (three orders of magnitude). Composites containing between 0.4 wt% and 0.55 wt% PAA showed a degradation rate of ˜1 mg / (min×cm 2 The degradation rate of the composite containing between 0.6 wt% and 1.4 wt% PAA showed ~0.2 mg / (min×cm 2 )’s water degradation rate.

[0082] In some embodiments, water degradation increases as the amount of at least one additional bioplastic increases relative to the amount of the at least one cross-linking material.

[0083] In some embodiments, water degradation is prevented or slowed or delayed as the amount of the at least one additional bioplastic is reduced relative to the amount of the at least one cross-linking material.

[0084] In some embodiments, the at least one cross-linking material and the at least one additional bioplastic are each present in a ratio of about 1:5. In some embodiments, the ratio is 1:5 PAA:PEO.

[0085] In some embodiments, the ratio is 2: 8. The ratio may be 2:8 PAA:PEO.

[0086] In some embodiments, the ratio between the amount of PEO and PAA combined and PVOH is 2:98, respectively. In other embodiments, the ratio between the amount of PEO and PAA combined and PCL and PVOH is 2:5:93 PEO / PAA:PCL:PVOH.

[0087] Alternatively or additionally, in the composition of the present invention, the amount of at least one cross-linking material may be between 0.4 wt% and 0.5 wt% or between 0.9 wt% and 1.1 wt%.

[0088] The mechanical properties of flexibility, rigidity and elongation can be similarly tailored by selecting appropriate relative amounts of PEO, PAA, cellulose and / or at least one inorganic salt. As known in the art, the flexibility or pliability of the composite is a measure of the rigidity of the product. The greater the flexibility of the product, the less rigid the product. Flexibility is measured as the resistance of the composite to deformation in response to a force applied to the composite. When the amount of PAA increases relative to the other components in the core formulation, the product becomes harder and less prone to elongation.

[0089] Table 1 provides an exemplary listing of compositions according to the present invention. As one may note, each composition may contain predetermined amounts of materials that impart desired properties to the composite prepared therefrom (as shown in Table 2).

[0090] An exemplary composite comprising 1% PAA and 5% cellulose material exhibited a lower sealing temperature than a composite comprising 1.5% PAA and 1% cellulose material. Similarly, a composite comprising 1% PAA and 5% cellulose material exhibited a faster water decomposition time (decomposed within 10-15 minutes as measured at room temperature under agitation) than a composite comprising 1.5% PAA and 1% cellulose material which showed a mid-range decomposition time (decomposed between 20-25 minutes as measured at room temperature under agitation).

[0091] Composites containing amounts of PAA in the range from 0.1 wt% to 2 wt% can be tailored to be more or less susceptible to water decomposition. The more PAA present (i.e., amounts close to the 2 wt% limit), the slower the water decomposition observed. Smaller amounts of PAA (i.e., amounts close to the 0.1 wt% limit) enable faster water decomposition.

[0092] In a similar manner, composites containing amounts of PEO ranging from 1 wt% to 10 wt% can be tailored to be more or less susceptible to water decomposition. The more PEO present (ie amounts approaching the 10 wt% limit), the faster the water decomposition is observed.

[0093]

[0094]

[0095] Table 1 - Exemplary compositions of the invention.

[0096] As shown in Tables 1 and 2, as the three relative amounts of PAA increase (see Table 1), the sealing temperature (i.e., the temperature required to adhere the two polymer materials) increases (see Table 2) and water degradation is delayed. As the amount of PEO increases, water degradation is accelerated (fast at room temperature under stirring).

[0097] Components Water degradation Sealing temperature Composition 1 quick medium Composition 2 quick medium Composition 3 medium medium Composition 4 medium medium Composition 5 slow high Composition 6 quick medium Composition 7 medium high Composition 8 medium high Composition 9 slow high Composition 10 slow high

[0098] Table 2 - Effect of increasing amounts of PVOH on composites produced from the compositions of the invention listed in Table 1.

[0099] Composition 6 and composition 9 contain the same amount of PEO, but composition 9 contains 5 times more PAA. As indicated in Table 2, the composites prepared from composition 9 decompose more slowly when in contact with water than the composites formed from composition 6, which degrade more quickly. The sealing temperature of the composites prepared from composition 6 is low, while the temperature of the composites from composition 9 is high, as expected with increasing amounts of PAA.

[0100] When Composition 6 was modified by increasing the amount of PAA to produce a composite composition such as Composition 7, the water dissolution rate decreased and the sealing temperature increased. This is also consistent with the decrease in dissolution rate due to the relative decrease in the amount of PEO.

[0101]

[0102]

[0103] Table 3 - Additional exemplary compositions of the invention

[0104] The exemplary composites comprising 1% PAA and 5% PCL exhibited lower sealing temperatures compared to composites comprising 2% PAA and 1% PCL. The composites comprising 1% PAA and 5% PEO exhibited faster water decomposition times (decomposed within 10-15 minutes as measured at room temperature under stirring) compared to composites comprising 2% PAA and 1% PEO, which showed slow range decomposition times (decomposed between 40-50 minutes as measured at room temperature under stirring).

[0105] As shown in Table 3, as the relative amount of PCL increases, the sealing temperature (i.e., the temperature required to adhere the two polymer materials) decreases. Compositions 17, 20, and 21 have moderate heat sealing temperatures, and compositions 18, 19, and 22 have much lower heat sealing temperatures. As the amount of PAA increases, the water decomposition time decreases (at room temperature with stirring). Therefore, compositions 14 and 21 have much higher water decomposition times. When using larger amounts of PAA, the amount of PEO can fine-tune the decomposition time-composition 13 dissolves faster than composition 11, and composition 16 has a higher dissolution rate than the dissolution rate of composition 15.

[0106] Thus, the composition of the present invention may contain an amount of PVOH between 80 wt% and 85 wt%; 80 wt% and 90 wt%; 80 wt% and 99 wt%; 85 wt% and 99 wt%; 90 wt% and 99 wt%; 78 wt% and 85 wt%; or between 78 wt% and 90 wt%.

[0107] In some embodiments, the amount of at least one cross-linking component is between 0.1 wt% and 1 wt%; 0.1 wt% and 2 wt%; 0.1 wt% and 4 wt%; 0.1 wt% and 5 wt%; 0.1 wt% and 7 wt%; 0.1 wt% and 10 wt%; 0.1 wt% and 12 wt%; 0.1 wt% and 15 wt%; 0.1 wt% and 17 wt%; 0.1 wt% and 0.2 wt%; 0.1 wt% and 0.3 wt%; 0.1 wt% and 0.4 wt%; 0. 1wt% and 0.5wt%; 0.1wt% and 0.6wt%; 0.1wt% and 0.7wt%; 0.1wt% and 0.8wt%; 0.1wt% and 0.9wt%; 1wt% and 20wt%; 3wt% and 20wt%; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%.

[0108] In some embodiments, the amount of at least one bioplastic is between 0.1wt% and 1wt%; 0.1wt% and 2wt%; 0.1wt% and 4wt%; 0.1wt% and 5wt%; 0.1wt% and 7wt%; 0.1wt% and 10wt%; 0.1wt% and 12wt%; 0.1wt% and 15wt%; 0.1wt% and 17wt%; 0.1wt% and 19wt%; 0.1wt% and 20wt%; 0.1wt% and 22wt% %; 0.1wt% and 25wt%; 0.1wt% and 27wt%; 0.1wt% and 30wt%; 0.1wt% and 32wt%; 0.1wt% and 35wt%; 0.1wt% and 37wt%; 0.1wt% and 40wt%; 0.1wt% and 43wt%; 0.1wt% and 45wt%; 0.1wt% and 47wt%; 1wt% and 5wt%; 1wt% and 7wt%; 1wt% and 10wt%; 1wt% and 1 2wt%; 1wt% and 15wt%; 1wt% and 17wt%; 1wt% and 20wt%; 1wt% and 22wt%; 1wt% and 25wt%; 1wt% and 27wt%; 1wt% and 30wt%; 1wt% and 32wt%; 1wt% and 35wt%; 1wt% and 37wt%; 1wt% and 40wt%; 1wt% and 42wt%; 1wt% and 45wt%; 1wt% and 47wt%; 3wt% and 20wt% ; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%; 5wt% and 20wt%; 5wt% and 25wt%; 5wt% and 30wt%; 5wt% and 35wt%; 5wt% and 40wt%; between 5wt% and 45wt%; or between 5wt% and 50wt%.

[0109] In some embodiments, the amount of at least one additive is between 0.1 wt% and 1 wt%; 0.1 wt% and 2 wt%; 0.1 wt% and 4 wt%; 0.1 wt% and 5 wt%; 0.1 wt% and 7 wt%; 0.1 wt% and 10 wt%; 0.1 wt% and 12 wt%; 0.1 wt% and 15 wt%; 0.1 wt% and 17 wt%; 0.1 wt% and 0.2 wt%; 0.1 wt% and 0.3 wt%; 0.1 wt% and 0.4 wt%; 0.1 wt% and 0.5wt%; 0.1wt% and 0.6wt%; 0.1wt% and 0.7wt%; 0.1wt% and 0.8wt%; 0.1wt% and 0.9wt%; 1wt% and 20wt%; 3wt% and 20wt%; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%.

[0110] In some embodiments, PVOH is used at 73wt%-96.5wt%, 68.5wt%-89.8wt%, 77.5wt%-96.3wt%, 67.5wt%-91.5wt%, 72wt%-95wt%, 71wt%-85wt%, 81wt%-90wt%, 68wt%-81wt%, 75wt%-84wt%, 60wt%-78wt%, 91.5wt%-99.3wt%. %, 87.5wt%-98.7wt%, 94.6wt%-82.5wt%, 87wt%-93.3wt%, 83wt%-98.7wt%, 78.5wt%-94.3wt%, 79.5wt%-93.8wt%, 68wt%-93.5wt%, 81.5wt%-93.7wt%, 73.5wt%-93.3wt%, 82wt%-98.6wt% or between 77.5wt%-9 8.2wt%; and at least one cross-linking compound is present in an amount between 0.1wt%-1.5wt%, 1.5wt%-2.5wt%, 1wt%-2.5wt%, 1.5wt%-4wt%, 1wt%, 1.5wt%-2wt%, 1.5wt%-2wt%, 5wt%, 0.1wt%-0.5wt%, 0.5wt%-2wt%, 0.1wt%-0.5wt%, or between 1wt%-2wt%. and / or at least one bioplastic is present in an amount between 1.5wt%-10wt%, 5wt%-10wt%, 1.5wt%-5wt%, 1.5wt%-4wt%, 5wt%, 2wt%, 10wt%, 0wt%-1wt%, 1wt%-5wt%, 5wt%-10wt%, 0.1wt%-1wt% or between 0.1wt%-1wt%, and wherein the composition optionally comprises at least one additive.

[0111] In some embodiments, the composition of the present invention comprises PVOH, PAA and PEO, respectively, in an amount selected from the following:

[0112] -73wt%-96.5wt%, 0.1wt%-1.5wt% and 1.5wt%-10wt%;

[0113] -68.5wt%-89.8wt%, 0.1wt%-1.5wt% and 5wt%-10wt%;

[0114] -77.5wt%-96.3wt%, 1.5wt%-2.5wt% and 1.5wt%-5wt%;

[0115] - 67.5wt%-91.5wt%, 1wt%-2.5wt% and 1.5wt%-5wt%;

[0116] -72wt%-95wt%, 1.5wt%-4wt% and 1.5wt%-4wt%;

[0117] -71wt%-85wt%, 1wt% and 5wt%;

[0118] -81wt%-90wt%, 1.5wt%-2wt% and 2wt%;

[0119] -68wt%-81wt%, 1.5wt%-2wt% and 5wt%;

[0120] -75wt%-84wt%, 5wt% and 5wt%;

[0121] -60wt%-78wt%, 5wt% and 10wt%;

[0122] -91.5wt%-99.3wt%, 0.1wt%-0.5wt% and 0wt%-1wt%;

[0123] -87.5wt%-98.7wt%, 0.1wt%-0.5wt% and 1wt%-5wt%;

[0124] -94.6wt%-82.5wt%, 0.1wt%-0.5wt% and 5wt%-10wt%;

[0125] -87wt%-93.3wt%, 0.5wt%-2wt% and 0wt%-1wt%;

[0126] -83wt%-98.7wt%, 0.5wt%-2wt% and 1wt%-5wt%;

[0127] -78.5wt%-94.3wt%, 0.5wt%-2wt% and 5wt%-10wt%;

[0128] -79.5wt%-93.8wt%, 0.1wt%-0.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%;

[0129] - 68wt%-93.5wt%, 0.1wt%-0.5wt% and 1wt%-5wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%;

[0130] -81.5wt%-93.7wt%, 0.1wt%-1.5wt% and 0wt%-1wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%;

[0131] -73.5wt%-93.3wt%, 0.5wt%-1.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%;

[0132] -82wt%-98.6wt%, 1wt%-2wt% and 0.1wt%-1wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%; or

[0133] - 77.5wt%-98.2wt%, 0.5wt%-1.5wt% and 0.1wt%-1wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%.

[0134] The compositions exemplified herein demonstrate and demonstrate a new process for improving at least one property of a solid composite material derived from a material composition as disclosed herein, such as a combination including poly(vinyl alcohol) (PVOH), poly(ethylene oxide) (PEO), and poly(acrylic acid) (PAA).

[0135] The composites of the present invention are said to be solid and can be manufactured as disclosed herein, with one or more improved properties. These properties can be imparted based on the intended use of the composite. The composites of the present invention can be manufactured into a variety of shapes and sizes and forms, and can be manufactured by a variety of processing techniques known in the field of polymeric materials.

[0136] Therefore, the present invention also contemplates a composite material in an unspecified form, comprising:

[0137] - at least one material selected from polymeric materials, the combination of which is susceptible to crosslinking. These polymers may be selected from poly(vinyl alcohol), poly(acrylic acid) and glutaraldehyde;

[0138] - at least one additional bioplastic material and is selected to be water insoluble. The material is also selected to be biodegradable. By including such a material, the amount of materials such as poly(vinyl alcohol), poly(acrylic acid) and glutaraldehyde can be reduced. The combination of the materials poly(vinyl alcohol), poly(acrylic acid) or glutaraldehyde with a biodegradable material selected from water insoluble materials is designed to fine tune the sensitivity to water. In some embodiments, the water insoluble material is selected from cellulose derived materials such as hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC) and / or chitosan;

[0139] - at least one material selected from hygroscopic materials. Such a material may be an ionic material such as a calcium salt, e.g. CaCl2; and

[0140] - At least one material selected from bioplastics. Non-limiting examples include PEO.

[0141] Also provided is a polymer composition, which in some embodiments is in the form of a solid composite, comprising poly(vinyl alcohol) (PVOH), poly(ethylene oxide) (PEO) and poly(acrylic acid) (PAA) (herein a core combination), optionally in combination with at least one material selected from an inorganic salt, a cellulose-derived substance, and chitosan.

[0142] The present invention also provides a raw material comprising poly(vinyl alcohol) (PVOH), poly(ethylene oxide) (PEO) and poly(acrylic acid) (PAA) and at least one material selected from inorganic salts, cellulose-derived substances, chitosan and formaldehyde.

[0143] In some embodiments, the composites of the present invention include poly(vinyl alcohol) (PVOH), poly(ethylene oxide) (PEO), poly(acrylic acid) (PAA), and at least one material selected from the group consisting of inorganic salts, cellulose-derived materials, chitosan, and formaldehyde.

[0144] The composites of the present invention can be prepared in any shape and form, as essentially one-dimensional objects, such as fibers; two-dimensional objects, such as sheets or films; or three-dimensional objects. In some embodiments, the composite is in the form of a sheet or film of material. In other embodiments, the composite is a three-dimensional product, which can be prepared by manipulating the composite sheet or film, or by any method selected from casting, blow molding, injection and injection molding, extrusion, and others. Non-limiting examples of three-dimensional products that can be manufactured include storage compartments and containers, boxes, pipes, pads, advertising stands and billboards, exhibition equipment and panels, automotive parts, bags, accessories, clothing pieces, tubes, rods, and others.

[0145] In some embodiments, the composition comprises:

[0146] A - Poly(vinyl alcohol) (PVOH) in an amount ranging between 30 wt% and 99 wt%.

[0147] In some embodiments, the amount of PVOH in the composition is between 30wt% and 40wt%; 30wt% and 45wt%; 30wt% and 50wt%; 30wt% and 55wt%; 30wt% and 60wt%; 30wt% and 65wt%; 30wt% and 70wt%; 30wt% and 75wt%; 30wt% and 80wt%; 30wt% and 85wt%; 30wt% and 90wt%; 40wt% and 45wt%; 40wt% and 50wt%; 40wt% and 60wt%; 40wt% and 70wt%; 40wt% and 80wt% ; 40wt% and 90wt%; 50wt% and 60wt%; 50wt% and 70wt%; 50wt% and 80wt%; 50wt% and 90wt%; 60wt% and 70wt%; 60wt% and 80wt%; 60wt% and 90wt%; 70wt% and 80wt%; 70wt% and 90wt%; 80wt% and 85wt%; 80wt% and 90wt%; 80wt% and 99wt%; 85wt% and 99wt%; 90wt% and 99wt%; between 78wt% and 85wt%; or between 78wt% and 90wt%.

[0148] B - at least one cross-linking compound selected from polymers, copolymers and non-polymeric materials in an amount ranging between 0.1 wt% and 20 wt%.

[0149] In some embodiments, the amount of this component in the composition of the present invention is between 0.1wt% and 1wt%; 0.1wt% and 2wt%; 0.1wt% and 4wt%; 0.1wt% and 5wt%; 0.1wt% and 7wt%; 0.1wt% and 10wt%; 0.1wt% and 12wt%; 0.1wt% and 15wt%; 0.1wt% and 17wt%; 0.1wt% and 0.2wt%; 0.1wt% and 0.3wt%; 0.1wt% and 0.4wt%; 0.1wt% and 0.5wt%; 0.1wt% and 0.6wt%; 0.1wt% and 0.7wt%; 0.1wt% and 0.8wt%; 0.1wt% and 0.9wt%; 1wt% and 20wt%; 3wt% and 20wt%; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%.

[0150] C - at least one bioplastic in an amount ranging between 0.1 wt% and 50 wt%.

[0151] In some embodiments, the amount of bioplastic is between 0.1wt% and 1wt%; 0.1wt% and 2wt%; 0.1wt% and 4wt%; 0.1wt% and 5wt%; 0.1wt% and 7wt%; 0.1wt% and 10wt%; 0.1wt% and 12wt%; 0.1wt% and 15wt%; 0.1wt% and 17wt%; 0.1wt% and 19wt%; 0.1wt% and 20wt%; 0.1wt% and 22wt%; 0.1wt% and 23wt%; 0.1wt% and 24wt%; 0.1wt% and 25wt%; 0.1wt% and 26wt%; 0.1wt% and 27wt%; 0.1wt% and 28wt%; 0.1wt% and 29wt%; 0.1wt% and 30wt%; 0.1wt% and 31wt%; 0.1wt% and 32wt%; 0.1wt% and 33wt%; 0.1wt% and 34wt%; 0.1wt% and 35wt%; 0.1wt% and 36wt%; 0.1wt% and 37wt% .1wt% and 25wt%; 0.1wt% and 27wt%; 0.1wt% and 30wt%; 0.1wt% and 32wt%; 0.1wt% and 35wt%; 0.1wt% and 37wt%; 0.1wt% and 40wt%; 0.1wt% and 43wt%; 0.1wt% and 45wt%; 0.1wt% and 47wt%; 1wt% and 5wt%; 1wt% and 7wt%; 1wt% and 10wt%; 1wt% and 12wt% t%; 1wt% and 15wt%; 1wt% and 17wt%; 1wt% and 20wt%; 1wt% and 22wt%; 1wt% and 25wt%; 1wt% and 27wt%; 1wt% and 30wt%; 1wt% and 32wt%; 1wt% and 35wt%; 1wt% and 37wt%; 1wt% and 40wt%; 1wt% and 42wt%; 1wt% and 45wt%; 1wt% and 47wt%; 3wt% and 20wt%; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%; 5wt% and 20wt%; 5wt% and 25wt%; 5wt% and 30wt%; 5wt% and 35wt%; 5wt% and 40wt%; between 5wt% and 45wt%; or between 5wt% and 50wt%.

[0152] D - at least one additive in an amount ranging between 0.1 wt% and 20 wt%.

[0153] In some embodiments, the amount of additives in the composition of the present invention is between 0.1wt% and 1wt%; 0.1wt% and 2wt%; 0.1wt% and 4wt%; 0.1wt% and 5wt%; 0.1wt% and 7wt%; 0.1wt% and 10wt%; 0.1wt% and 12wt%; 0.1wt% and 15wt%; 0.1wt% and 17wt%; 0.1wt% and 0.2wt%; 0.1wt% and 0.3wt%; 0.1wt% and 0.4wt%; 0.1wt% and 0.5wt%; 0.1wt% and 0.6wt%; 0.1wt% and 0.7wt%; 0.1wt% and 0.8wt%; 0.1wt% and 0.9wt%; 1wt% and 20wt%; 3wt% and 20wt%; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%.

[0154] In some embodiments, the composition of the present invention comprises 73wt%-96.5wt%, 68.5wt%-89.8wt%, 77.5wt%-96.3wt%, 67.5wt%-91.5wt%, 72wt%-95wt%, 71wt%-85wt%, 81wt%-90wt%, 68wt%-81wt%, 75wt%-84wt%, 60wt%-78wt%, 91.5wt%-99.3wt%, 87 .5wt%-98.7wt%, 94.6wt%-82.5wt%, 87wt%-93.3wt%, 83wt%-98.7wt%, 78.5wt%-94.3wt%, 79.5wt%-93.8wt%, 68wt%-93.5wt%, 81.5wt%-93.7wt%, 73.5wt%-93.3wt%, 82wt%-98.6wt% or between 77.5wt%-98.2wt% an amount of PVOH; and an amount of at least one cross-linking compound as disclosed herein in an amount between 0.1 wt%-1.5 wt%, 1.5 wt%-2.5 wt%, 1 wt%-2.5 wt%, 1.5 wt%-4 wt%, 1 wt%, 1.5 wt%-2 wt%, 1.5 wt%-2 wt%, 5 wt%, 0.1 wt%-0.5 wt%, 0.5 wt%-2 wt%, 0.1 wt%-0.5 wt%, or between 1 wt%-2 wt%; and / or At least one bioplastic in an amount between 1.5wt%-10wt%, 5wt%-10wt%, 1.5wt%-5wt%, 1.5wt%-4wt%, 5wt%, 2wt%, 10wt%, 0wt%-1wt%, 1wt%-5wt%, 5wt%-10wt%, 0.1wt%-1wt% or between 0.1wt%-1wt%, and the total amount of the components (including additives, if present) is scaled up (or summed) to 100%.

[0155] In some embodiments, the compositions of the present invention may further comprise at least one additive.

[0156] In some embodiments, the compositions of the present invention comprise materials from groups (A), (B), and (C) above, such as PVOH, PAA, and PEO, respectively:

[0157] -73wt%-96.5wt%, 0.1wt%-1.5wt% and 1.5wt%-10wt%;

[0158] -68.5wt%-89.8wt%, 0.1wt%-1.5wt% and 5wt%-10wt%;

[0159] -77.5wt%-96.3wt%, 1.5wt%-2.5wt% and 1.5wt%-5wt%;

[0160] - 67.5wt%-91.5wt%, 1wt%-2.5wt% and 1.5wt%-5wt%;

[0161] -72wt%-95wt%, 1.5wt%-4wt% and 1.5wt%-4wt%;

[0162] -71wt%-85wt%, 1wt% and 5wt%;

[0163] -81wt%-90wt%, 1.5wt%-2wt% and 2wt%;

[0164] -68wt%-81wt%, 1.5wt%-2wt% and 5wt%;

[0165] -75wt%-84wt%, 5wt% and 5wt%;

[0166] -60wt%-78wt%, 5wt% and 10wt%;

[0167] -91.5wt%-99.3wt%, 0.1wt%-0.5wt% and 0wt%-1wt%;

[0168] -87.5wt%-98.7wt%, 0.1wt%-0.5wt% and 1wt%-5wt%;

[0169] -94.6wt%-82.5wt%, 0.1wt%-0.5wt% and 5wt%-10wt%;

[0170] -87wt%-93.3wt%, 0.5wt%-2wt% and 0wt%-1wt%;

[0171] -83wt%-98.7wt%, 0.5wt%-2wt% and 1wt%-5wt%;

[0172] -78.5wt%-94.3wt%, 0.5wt%-2wt% and 5wt%-10wt%;

[0173] -79.5wt%-93.8wt%, 0.1wt%-0.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%;

[0174] - 68wt%-93.5wt%, 0.1wt%-0.5wt% and 1wt%-5wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%;

[0175] -81.5wt%-93.7wt%, 0.1wt%-1.5wt% and 0wt%-1wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%;

[0176] -73.5wt%-93.3wt%, 0.5wt%-1.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%;

[0177] -82wt%-93.8wt%, 0.1wt%-0.5wt% and 0.1wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%;

[0178] - 77.5wt%-98.2wt%, 0.5wt%-1.5wt% and 0.1wt%-1wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%.

[0179] The present invention also provides a process for manufacturing an object or composite according to the present invention. The process improved according to the production rules provided herein comprises:

[0180] - forming a core composition comprising PAA and PEO; and

[0181] - treating the core composition with a composition comprising PVOH and any additional materials discussed herein under conditions that allow for compounding of all components into a single homogeneous composition and processing of the composition to produce a 1D object, a 2D object or a 3D object.

[0182] The present invention also provides a process, comprising:

[0183] - forming a core composition, for example comprising PVOH, PEO and PAA;

[0184] - treating the core composition with at least one additional material as above, e.g. selected from inorganic salts, cellulose derived substances, chitosan and formaldehyde, under conditions allowing compounding of all components into a single homogeneous composition and processing of the composition to produce a 1D object, a 2D object or a 3D object.

[0185] As stated herein, for example, in order to adjust the water decomposition rate, a compound containing an amount of PAA in a range from 0.1 wt% to 2 wt% can be tailored to be more or less susceptible to water decomposition. The more PAA there is (i.e., an amount close to the 2 wt% limit), the slower the water decomposition is observed. Smaller amounts of PAA (i.e., amounts close to the 0.1 wt% limit) enable faster water decomposition. In a similar manner, a compound containing an amount of PEO in a range from 1 wt% to 10 wt% can be tailored to be more or less susceptible to water decomposition. The more PEO there is (i.e., an amount close to the 10 wt% limit), the faster the water decomposition is observed. At a fixed PAA concentration, a smaller amount of PEO (i.e., an amount close to the 1.5 wt% limit) enables slower water decomposition.

[0186] In some embodiments, the process includes the step of providing a formulation comprising PVOH.

[0187] In some embodiments, a formulation comprising PVOH is added to or combined with a preformulated formulation comprising PEO, and in some embodiments, the combined formulations are allowed to mix to provide a homogenous formulation.

[0188] In some embodiments, the PVOH-PEO formulation is added to or combined with a preformulation of PAA under conditions that allow PAA and PVOH to crosslink. In some embodiments, crosslinking is achieved by adding at least one acid at a temperature between room temperature (RT, 23°C to 30°C) and 230°C (or between 120°C and 150°C, or between 150°C and 230°C). In some embodiments, the temperature is between 50°C and 150°C or between 150°C and 230°C. In some embodiments, the acid may be selected from inorganic acids and organic acids. In some embodiments, the acid is selected from sulfuric acid, HCl, nitric acid, and other acids. In some embodiments, the combination of PVOH, PEO, and PAA is further treated with or combined with at least one inorganic salt. In some embodiments, the inorganic salt is as defined above.

[0189] In some embodiments, the combination of PVOH, PEO, and PAA is further treated with or combined with PVOH and at least one cellulose-based material selected as described above.

[0190] Compounding the components together into a single homogeneous composition can be carried out under mixing at room temperature (23°C to 30°C) and temperatures between 120°C-230°C or 150°C and 230°C. When the homogeneous composition is formed, it can be manipulated or processed under industrially acceptable conditions to obtain the final composite product. Such processes may involve one or more of casting, blow molding, injection and extrusion.

[0191] The present invention also provides exemplary composites as prepared and characterized herein, formed from the compositions listed in Table 1 and Table 3. Thus, the present invention also contemplates the compositions listed in Table 1 and Table 3, which are designated herein as Composition 1 to Composition 22.

[0192] Also provided are composites formulated from the above compositions as defined, said compositions being designated as Composition 1 to Composition 22.

[0193] According to the process of the present invention, the final product produced by the raw materials comprising PVOH, PEO and PAA and optionally one or more additional materials (e.g., selected from inorganic salts, cellulose-derived substances, chitosan and glycerol) can be endowed with a desired property or a set of properties by improving, fine-tuning or tweaking its production process. The process can be modified by changing the material ratio between two or more components (i.e., PVOH, PEO and PAA) contained in the core combination or between any component of the core combination and any other component of the material combination (e.g., inorganic salts, cellulose-derived substances, chitosan and glycerol), by changing the additional components added to the core combination, by changing or modifying the processing conditions of the process for manufacturing the solid product, or by selecting a specific process sequence. Examples of the effects of these modifications on the properties of the final solid product are provided below.

[0194] The process includes a step of controlling (a) the weight / weight ratio (w / w) between two or more materials selected from PVOH, PEO and PAA, or (b) the weight / weight ratio (w / w) between at least one material selected from PVOH, PEO and PAA and at least one other material selected from inorganic salts, cellulose-derived substances, chitosan and formaldehyde, providing an option for improving the properties of the solid composite by selecting the material ratio between any two materials in the core combination comprising PVOH, PEO and PAA, for example, the ratio between PVOH and PEO, or PVOH and PAA, or PEO and PAA, or the ratio between any one of PVOH, PEO and PAA and any one of inorganic salts, cellulose-derived substances, chitosan and formaldehyde. Non-limiting material pairs whose relative weight amounts (in grams or wt %) have an effect on at least one property of the solid final product include PVOH and PEO, PVOH and PAA, PEO and PAA, PVOH and an inorganic salt, PVOH and a cellulose-containing material, PVOH and chitosan, PVOH and formaldehyde, PEO and an inorganic salt, PEO and a cellulose-derived material, PEO and chitosan, PEO and formaldehyde, PAA and an inorganic salt, PAA and a cellulose-derived material, PAA and chitosan, and PAA and formaldehyde.

[0195] As demonstrated in the examples provided herein, increasing the amount of inorganic salt (such as a calcium salt, e.g., calcium chloride) relative to at least one component of the core combination results in an increase in the elongation ability of a solid product obtained from a composition comprising the core combination and at least one inorganic salt.

[0196] In a similar manner, increasing the amount of PVOH relative to PAA increases the OTR. Increasing the amount of PAA relative to PVOH increases the stiffness.

[0197] In addition, modifying the relative amount of PEO has an impact on the stability of the product against water. Increasing the amount of PEO relative to PAA or PVOH increases water solubility (or reduces water resistance and increases water degradability) and increases the flexibility of the material. Similarly, increasing the amount of cellulose-derived materials (such as HPMC) relative to any core component reduces the water solubility of the solid final product.

[0198] exist Figure 1 Embodiments of the invention that demonstrate the ability to modulate some of the properties described herein are depicted in .

[0199] As used herein, the term "ratio", "material ratio" or "w / w ratio" refers to the amount of material of one component of a combination (in the total weight of the combination) relative to the amount of material of another component of the combination (in the total weight of the combination). For example, the ratio between PVOH and PEO is related to the relative amount of PVOH compared to the amount of PEO in the combination. The ratio is provided as an absolute weight value. For example, a ratio of 1:1 PVOH:PEO indicates the same amount of each component in the combination. An increasing ratio stated with respect to one of the components means an increase in the amount of that particular component relative to the other component. When, for example, the amount of PVOH increases relative to PEO, the stated ratio may be greater than 1:1, such as 2:1 or higher. When the term "about" is used with respect to an indicated ratio or amount, it means a ratio or amount of ±10% of the indicated value. For example, a ratio of about 1:1 is a ratio between (0.9 and 1.1):(1.1 and 0.9).

[0200] Therefore, in another aspect of the present invention, there is provided a process for making a solid composite material having a predetermined water decomposition rate, the process comprising:

[0201] - In a process for making a solid composite material, controlling a weight / weight ratio (w / w) between:

[0202] - (a) two or more materials selected from poly(vinyl alcohol) (PVOH), poly(ethylene oxide) (PEO) and poly(acrylic acid) (PAA), or

[0203] - (b) between at least one material selected from PVOH, PEO and PAA and at least one other material selected from inorganic salts, cellulose-derived substances, chitosan and formaldehyde.

[0204] In some embodiments, the "predetermined water decomposition rate" is the rate at which the composite of the present invention decomposes when in contact with water. The rate can be measured in units of grams per minute, or simply measured in the number of minutes it takes for the article to begin to decompose. As stated herein, the composite containing the amount of PAA in the range of from 0.1wt% to 2wt% can be tailored to be more or less susceptible to water decomposition. The more PAA there is (i.e., the amount close to the 2wt% extreme), the slower the observed water decomposition. Smaller amounts of PAA (i.e., the amount close to the 0.1wt% extreme) can achieve faster water decomposition. In a similar manner, the composite containing the amount of PEO in the range of from 1.5wt% to 10wt% can be tailored to be more or less susceptible to water decomposition. The more PEO there is (i.e., the amount close to the 10wt% extreme), the faster the observed water decomposition. Smaller amounts of PEO (i.e., the amount close to the 1.5wt% extreme) can achieve slower water decomposition.

[0205] Thus, in some embodiments, a process for making a solid composite material having a predetermined water decomposition rate comprises:

[0206] (a) modifying the amount of PAA to be between 0.1 wt% and 2 wt%, wherein the higher the amount of PAA in the composite (between 1 wt% and 2 wt%), the slower the water decomposition, and wherein the lower the amount of PAA (between 0.1 wt% and 1 wt%), the faster the water decomposition; or

[0207] (b) Modifying the amount of PEO to be between 1.5wt% and 10wt%, where the amount of PEO in the composite is high (between 3wt% and 10wt%), the water decomposition is faster, and where the amount of PEO is low (between 1.5wt% and 3wt%), the water decomposition is slow.

[0208] In some embodiments, composites containing between 0.4 wt% and 0.55 wt% PAA in PVOH show ~1 mg / (min×cm 2 ) degradation rate. Composites containing between 0.6 wt% and 1.4 wt% PAA in PVOH showed ~0.2 mg / (min×cm 2 )’s water degradation rate.

[0209] Also provided is a process for improving at least one property of a solid composite material formed from a composition according to the present invention, the process comprising treating a composition comprising an amount of PAA and an amount of PEO with a composition comprising an amount of PVOH and optionally at least one additive, wherein the amount of PAA, the amount of PEO and optionally the amount of PVOH are selected to improve at least one property under conditions that allow the PAA, PEO and PVOH and optionally the at least one additive to be compounded into a solid composite having at least one property.

[0210] In some embodiments, the at least one property is water degradation.

[0211] In some embodiments, the amount of PAA and the amount of PEO are in a ratio of about 1:5, respectively.

[0212] In some embodiments, the amount of PAA and the amount of PEO are in a ratio of about 2: 8. In some embodiments, the ratio is 2:8 PAA:PEO.

[0213] In some embodiments, the ratio between the amount of PEO and the amount of PAA combined and the amount of PVOH is 2:98, respectively.

[0214] In some embodiments, the ratio between the amount of PEO and the amount of PAA combined and the amount of PCL and the amount of PVOH is 2:5:93 PEO / PAA:PCL:PVOH.

[0215] In some embodiments, the amount of PAA is between 0.4 wt% and 0.5 wt%.

[0216] In some embodiments, the amount of PAA is between 0.9 wt% and 1.1 wt%.

[0217] In some embodiments, the amount of PVOH is between 80 wt% and 85 wt%; 80 wt% and 90 wt%; 80 wt% and 99 wt%; 85 wt% and 99 wt%; 90 wt% and 99 wt%; 78 wt% and 85 wt%; or between 78 wt% and 90 wt%.

[0218] In some embodiments, the amount of PAA is between 0.1 wt% and 1 wt%; 0.1 wt% and 2 wt%; 0.1 wt% and 4 wt%; 0.1 wt% and 5 wt%; 0.1 wt% and 7 wt%; 0.1 wt% and 10 wt%; 0.1 wt% and 12 wt%; 0.1 wt% and 15 wt%; 0.1 wt% and 17 wt%; 0.1 wt% and 0.2 wt%; 0.1 wt% and 0.3 wt%; 0.1 wt% and 0.4 wt%; 0.1 wt% and 0.5 wt%; % and 0.5wt%; 0.1wt% and 0.6wt%; 0.1wt% and 0.7wt%; 0.1wt% and 0.8wt%; 0.1wt% and 0.9wt%; 1wt% and 20wt%; 3wt% and 20wt%; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%.

[0219] In some embodiments, the amount of PEO is between 0.1wt% and 1wt%; 0.1wt% and 2wt%; 0.1wt% and 4wt%; 0.1wt% and 5wt%; 0.1wt% and 7wt%; 0.1wt% and 10wt%; 0.1wt% and 12wt%; 0.1wt% and 15wt%; 0.1wt% and 17wt%; 0.1wt% and 19wt%; 0.1wt% and 20wt%; 0.1wt% and 22wt%; 0.1wt% and 23wt%; 0.1wt% and 24wt%; 0.1wt% and 25wt%; 0.1wt% and 26wt%; 0.1wt% and 27wt%; 0.1wt% and 28wt%; 0.1wt% and 29wt%; 0.1wt% and 30wt%; 0.1wt% and 31wt%; 0.1wt% and 32wt%; 0.1wt% and 33wt%; 0.1wt% and 34wt%; 0.1wt% and 35wt%; 0.1wt% and 36wt%; 0.1wt% and 37wt%; 0.1wt% and 38wt%; 0.1wt% and 39wt% .1wt% and 25wt%; 0.1wt% and 27wt%; 0.1wt% and 30wt%; 0.1wt% and 32wt%; 0.1wt% and 35wt%; 0.1wt% and 37wt%; 0.1wt% and 40wt%; 0.1wt% and 43wt%; 0.1wt% and 45wt%; 0.1wt% and 47wt%; 1wt% and 5wt%; 1wt% and 7wt%; 1wt% and 10wt%; 1wt% and 12wt% t%; 1wt% and 15wt%; 1wt% and 17wt%; 1wt% and 20wt%; 1wt% and 22wt%; 1wt% and 25wt%; 1wt% and 27wt%; 1wt% and 30wt%; 1wt% and 32wt%; 1wt% and 35wt%; 1wt% and 37wt%; 1wt% and 40wt%; 1wt% and 42wt%; 1wt% and 45wt%; 1wt% and 47wt%; 3wt% and 20wt%; 5wt% and 20wt%; 7wt% and 20wt%; 9wt% and 20wt%; 10wt% and 20wt%; 12wt% and 20wt%; between 15wt% and 20wt%; or between 17wt% and 20wt%; 5wt% and 20wt%; 5wt% and 25wt%; 5wt% and 30wt%; 5wt% and 35wt%; 5wt% and 40wt%; between 5wt% and 45wt%; or between 5wt% and 50wt%.

[0220] In some embodiments, PVOH is present in an amount of 73 wt% to 96.5 wt%, 68.5 wt% to 89.8 wt%, 77.5 wt% to 96.3 wt%, 67.5 wt% to 91.5 wt%, 72 wt% to 95 wt%, 71 wt% to 85 wt%, 81 wt% to 90 wt%, 68 wt% to 81 wt%, 75 wt% to 84 wt%, 60 wt% to 78 wt%, 91.5 wt% to 99.3 wt%, 87.5wt%-98.7wt%, 94.6wt%-82.5wt%, 87wt%-93.3wt%, 83wt%-98.7wt%, 78.5wt%-94.3wt%, 79.5wt%-93.8wt%, 68wt%-93.5wt%, 81.5wt%-93.7wt%, 73.5wt%-93.3wt%, 82wt%-98.6wt% or between 77. %-2wt%, 0.1wt%-0.5wt%, 0.5wt%-2wt%, 0.1wt%-0.5wt%, or between 1wt%-2wt%; and PAA is present in an amount between 0.1wt%-1.5wt%, 1.5wt%-2.5wt%, 1wt%-2.5wt%, 1.5wt%-4wt%, 1wt%, 1.5wt%-2wt%, 1.5wt%-2wt%, 5wt%, 0.1wt%-0.5wt%, 0.5wt%-2wt%, 0.1wt%-0.5wt%, or between 1wt%-2wt%. and / or PEO is present in an amount between 1.5wt%-10wt%, 5wt%-10wt%, 1.5wt%-5wt%, 1.5wt%-4wt%, 5wt%, 2wt%, 10wt%, 0wt%-1wt%, 1wt%-5wt%, 5wt%-10wt%, 0.1wt%-1wt% or between 0.1wt%-1wt%, and wherein the composition optionally comprises at least one additive.

[0221] In some embodiments, the composition comprises PVOH, PAA, and PEO, respectively, in amounts selected from:

[0222] -73wt%-96.5wt%, 0.1wt%-1.5wt% and 1.5wt%-10wt%;

[0223] -68.5wt%-89.8wt%, 0.1wt%-1.5wt% and 5wt%-10wt%;

[0224] -77.5wt%-96.3wt%, 1.5wt%-2.5wt% and 1.5wt%-5wt%;

[0225] - 67.5wt%-91.5wt%, 1wt%-2.5wt% and 1.5wt%-5wt%;

[0226] -72wt%-95wt%, 1.5wt%-4wt% and 1.5wt%-4wt%;

[0227] -71wt%-85wt%, 1wt% and 5wt%;

[0228] -81wt%-90wt%, 1.5wt%-2wt% and 2wt%;

[0229] -68wt%-81wt%, 1.5wt%-2wt% and 5wt%;

[0230] -75wt%-84wt%, 5wt% and 5wt%;

[0231] -60wt%-78wt%, 5wt% and 10wt%;

[0232] -91.5wt%-99.3wt%, 0.1wt%-0.5wt% and 0wt%-1wt%;

[0233] -87.5wt%-98.7wt%, 0.1wt%-0.5wt% and 1wt%-5wt%;

[0234] -94.6wt%-82.5wt%, 0.1wt%-0.5wt% and 5wt%-10wt%;

[0235] -87wt%-93.3wt%, 0.5wt%-2wt% and 0wt%-1wt%;

[0236] -83wt%-98.7wt%, 0.5wt%-2wt% and 1wt%-5wt%;

[0237] -78.5wt%-94.3wt%, 0.5wt%-2wt% and 5wt%-10wt%;

[0238] -79.5wt%-93.8wt%, 0.1wt%-0.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%;

[0239] - 68wt%-93.5wt%, 0.1wt%-0.5wt% and 1wt%-5wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%;

[0240] -81.5wt%-93.7wt%, 0.1wt%-1.5wt% and 0wt%-1wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%;

[0241] -73.5wt%-93.3wt%, 0.5wt%-1.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%;

[0242] -82wt%-98.6wt%, 1wt%-2wt% and 0.1wt%-1wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%; or

[0243] - 77.5wt%-98.2wt%, 0.5wt%-1.5wt% and 0.1wt%-1wt%; and optionally further comprising PCL in an amount ranging between 5wt%-10wt%.

[0244] Thus, the degradation profile, i.e., the speed or rate at which the composite decomposes upon contact with water, and potentially how the degradation occurs, will depend on any of the factors disclosed herein. In some embodiments, water degradation is adjusted by increasing the amount of PEO relative to PAA, thereby increasing water degradation. In some embodiments, water degradation is adjusted by increasing the amount of PAA relative to PEO, thereby decreasing water degradation. In other embodiments, water degradation is adjusted by decreasing the amount of PEO relative to PAA, thereby decreasing water degradation. In other embodiments, water degradation is adjusted by decreasing the amount of PAA relative to PEO, thereby increasing water degradation.

[0245] An increase in the amount of PEO or PAA relative to the amount of PAA or PEO does not necessarily mean increasing the amount of PEO / PAA above the amount of PAA / PEO, the increase in amount should be sufficient to increase / decrease water degradation. The extent of the increase / decrease in amount depends, among other things, on the initial amount of PEO / PAA in the composition, additional effects associated with the increase / decrease in the amount of PEO / PAA, the desired degradation profile and other factors.

[0246] The present invention also provides a process for adjusting the water degradation profile of a solid composite material formed from a composition according to the present invention, the process comprising treating a composition comprising an amount of PAA and an amount of PVOH and optionally at least one additive with an effective amount of PEO, the effective amount being selected to increase or decrease the water degradation of the solid composite, wherein the process is carried out under conditions that allow the PAA, PEO and PVOH and optionally at least one additive to be compounded into a solid composite having a water degradation profile.

[0247] Also provided is a process for setting the onset of water degradation of a solid composite comprising PVOH, the process comprising:

[0248] - when preparing the composition comprising PVOH, at least one cross-linking material and at least one additional bioplastic, selecting an amount of at least one cross-linking material and an amount of at least one additional bioplastic that in combination accelerates or delays water degradation of the solid composite, and

[0249] - heat treating the composition to form a solid composite.

[0250] As used herein, the expression "setting the onset of water degradation" means predetermining the rate at which the composite will decompose, or in other words, whether the composite will exhibit immediate degradation, delayed degradation, or no water degradation in water. By selecting the components of the composition from which the composite is prepared, the onset of degradation can be predetermined by a simple experimental protocol, as disclosed herein. As disclosed herein, determining the rate of decomposition can be used to determine the earliest point at which the composite will degrade and degrade. Without wishing to be bound by theory or decomposition mechanism, and depending on the form of the composite, such as a film or a particle, a degradation cascade can be concluded and the onset of decomposition determined. For example, in the degradation of a composite in the form of a film, the initial deformation may be accompanied by tearing of the film, breaking into particles, and subsequent dissolution. Therefore, the onset of degradation can be reclassified as an initial deformation stage.

[0251] Thus, the process of the present invention is configured to produce a polymer composite according to the present invention. The composite can be prepared by about 1 mg / (min×cm 2 ), or about 0.2 mg / (min×cm 2 ) or at 0.001mg / (min×cm 2 ) to 5mg / (min×cm 2 ) or more. Some of the composites can be configured to degrade immediately, while others can be configured to degrade days, weeks, or months after manufacture; and other composites may also be prepared to not degrade.

[0252] As stated, the process of the invention may include the step of forming the composite into a desired form, for example in the form of pellets, in the form of a masterbatch, in the form of a 1D object, a 2D object or a 3D object.

[0253] Also provided are objects comprising or consisting of the composite of the invention as disclosed herein and uses thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0254] For a better understanding of the subject matter disclosed herein and in order to illustrate how the subject matter disclosed herein may be carried out in practice, embodiments will now be described, by way of non-limiting examples only, with reference to the accompanying drawings, in which:

[0255] Figure 1is a schematic representation of an embodiment of the present invention that demonstrates the ability to tune the properties of a composite material.

[0256] Figure 2 The effect of PAA on the dissolution of PVOH is demonstrated.

[0257] Figure 3 The effect of PEO on the dissolution of PVOH is demonstrated. DETAILED DESCRIPTION OF THE INVENTION

[0259] Embodiment 1:

[0260] PAA and ground thermoplastic PVOH were mixed in a ratio of 1:99 and extruded using a L / D 40 twin screw co-rotating extruder at 50 rpm and 190-210° C. through a 3 mm diameter circular die and the outgoing polymer strands were passed through an air cooling system and a pelletizer.

[0261] Embodiment 2:

[0262] PAA, HPMC and ground thermoplastic PVOH were mixed in a ratio of 1:10:89 and extruded through a 3 mm diameter circular die using a L / D 40 twin screw co-rotating extruder at 50 rpm and 190-210°C, and the outgoing polymer strands were passed through an air cooling system and a pelletizer.

[0263] Embodiment 3:

[0264] PEO and PAA were mixed together in a ratio of 8:2 and extruded through a 3 mm diameter circular die using a L / D 40 twin screw co-rotating extruder at 150 rpm and 80°C, and the polymer strands that came out were passed through an air cooling system and a pelletizer. The resulting PEO / PAA pellets were further mixed with PVOH in a ratio of 2:98 and extruded through a 3 mm diameter circular die using a L / D 40 twin screw co-rotating extruder equipped with a devolatilization system at 50 rpm and 190-210°C, and the polymer strands that came out were passed through an air cooling system and a pelletizer.

[0265] Embodiment 4:

[0266] PEO and PAA were mixed together in a ratio of 8:2 and extruded through a 3 mm diameter circular die using a L / D 40 twin screw co-rotating extruder at 150 rpm and 80°C, and the polymer strands that came out were passed through an air cooling system and a pelletizer. The resulting PEO / PAA pellets were further mixed with PCL and PVOH in a ratio of 2:5:93 and extruded through a 3 mm diameter circular die using a L / D 40 twin screw co-rotating extruder equipped with a devolatilization system at 50 rpm and 190-210°C, and the polymer strands that came out were passed through an air cooling system and a pelletizer.

[0267] Figure 2 The effect of PAA on the dissolution of PVOH is demonstrated. Compounds with 0%, 0.5%, 1%, 1.5% and 2% PAA in PVOH were produced by reactive extrusion. Samples were then pressed to 200 microns from each compound and the dissolution was studied under stirring at room temperature. The time for initial deformation (D), tearing (T), breaking into particles in water (P) and solubility (S) of the film were recorded. In general, deformation, tearing, breaking into particles and solubility were delayed as the concentration of PAA in the compound increased.

[0268] Figure 3 Demonstrate the influence of PEO on PVOH dissolution.Produce compound with 0%, 1%, 5% and 10% PEO in PVOH, with constant concentration of PAA (0.5%) by reaction extrusion.Then sample is pressed to 200 microns from each compound, and dissolution is studied under stirring at room temperature.Record the time of initial deformation (D), tearing (T), breaking into particles (P) and solubility (S) of film.In general, deformation, tearing, breaking into particles and solubility are accelerated as the concentration of PEO in compound increases.

[0269] In addition to the dissolution kinetics, some physical and mechanical parameters of the compound were characterized (data not shown). The polymer pellets were processed into 100 extruded films on a 200°C film casting extruder. According to ASTM E171 / 71M-11 (re-approved in 2015), the cast film was conditioned at 23an°C and 50andard for 48 hours. The test was carried out under the same temperature / humidity conditions as mentioned. The tensile properties of the film were determined according to the Standard Test Method for Tensile Properties of Thin Plastic Sheeting for Thin Plastic Sheeting used for the tensile properties of thin plastic sheets. For this purpose, according to the procedure B specified in ASTM D6287-17 for cutting film and sheet test specimens, a strip sample of 25.4 mm wide and 250 mm long was cut from the film using a double blade shared cutter. Five samples were tested for each film. A tensile tester LLOYD INSTRUMENTS (UK) LRX 5K with a 500N load cell and wire clamps according to ASTM D882 was used in the test. The initial distance between the clamps was 100 mm. All samples were tested along the film machine direction (MD) with a clamp separation rate of 500 mm / min. According to these measurements, increasing the PAA content in the compound increases the tensile strength, breaking stress and Young's modulus, while the elongation at break decreases.

[0270] The exemplary composites containing 1% PAA exhibited higher tensile strength, stress at break, and Young's modulus than the composites containing 0.5% PAA, and the elongation at break of the composites containing 1% PAA was lower than that of the composites containing 0.5% PAA.

[0271] Another exemplary composite comprising 1% PAA exhibits lower tensile strength, stress at break, and Young's modulus than the composite comprising 1.5% PAA, and the elongation at break of the composite comprising 1% PAA is higher than that of the composite comprising 1.5% PAA.

[0272] Another exemplary composite comprising 0.5% PAA exhibits higher tensile strength, stress at break, and Young's modulus than the composite comprising no PAA, and the elongation at break of the composite comprising 0.5% PAA is lower than the elongation at break of the composite comprising no PAA.

Claims

1. A composition comprising the following anhydrous combination: A - poly(vinyl alcohol) (PVOH) in an amount ranging between 78 wt% and 99 wt%; B - at least one crosslinking compound present in an amount ranging between 0.1 wt% and 7 wt%, the crosslinking compound having functional groups capable of associating with PVOH, wherein the crosslinking compound is a carboxylic acid compound selected from dicarboxylic acids, tricarboxylic acids and higher homologs; C - at least one additional bioplastic in an amount ranging between 0.1 wt% and 50 wt%, the at least one additional bioplastic being a biodegradable polymer, wherein the at least one additional bioplastic is selected from the group consisting of poly(ethylene oxide) (PEO), poly(ethylene glycol) (PEG), polycaprolactone (PCL), poly(lactic acid) (PLA), cellulose and cellulose derivatives, starch, chitosan and polyhydroxyalkanoates (PHA); and D - optionally, at least one additive in an amount ranging between 0.1 wt% and 20 wt%; The sum of the contents of each component in the composition is 100%; The amounts of the PVOH, the at least one cross-linking compound, and the at least one additional bioplastic are selected to modulate water degradation of a composite formed from the composition.

2. The composition according to claim 1, wherein the at least one cross-linking compound is selected from polymeric or non-polymeric materials.

3. The composition of claim 2, wherein the polymer is selected from a copolymer or an ionomer.

4. The composition of claim 2, wherein the polymer is a polyacid.

5. The composition of claim 4, wherein the polyacid is poly(acrylic acid) (PAA) or poly(methacrylic acid) (PMAA).

6. The composition of claim 1, wherein the at least one cross-linking compound is PAA.

7. The composition of claim 1, wherein the at least one crosslinking compound is a polymer grafted with anhydride.

8. The composition of claim 2, wherein the polymer is selected from poly(ethylene-co-acrylic acid) (PE-co-AA), poly(ethylene-co-methacrylic acid) (PE-co-MAA), poly(lactide-block-acrylic acid) (PLA-block-AA), PVOH with carboxyl groups, and carboxymethyl cellulose (CMC).

9. The composition of claim 8, wherein the polymer is poly(ethylene-co-acrylic acid).

10. The composition of claim 1, wherein the PHA is polyhydroxybutyrate (PHB).

11. The composition of claim 1, wherein the cellulose derivative is selected from the group consisting of nanocrystalline cellulose (NCC), microfibrillar cellulose, bacterial cellulose, hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC) and carboxymethyl cellulose (CMC).

12. The composition of claim 1, wherein the at least one additional bioplastic is PEO.

13. The composition of claim 1, wherein the at least one additional bioplastic is PCL.

14. The composition of claim 1, wherein the at least one additional bioplastic is PEG.

15. The composition of claim 1, comprising PEO and PCL.

16. The composition according to any one of claims 1 to 9, comprising PVOH, PAA, PEO and optionally PCL.

17. The composition of claim 1, wherein the at least one additive is selected from fillers, reinforcing agents, slip agents, light stabilizers, UV absorbers, flame retardants, antimicrobial agents, antiviral agents, foaming agents, nucleating agents, antioxidants, anti-caking agents, and antistatic agents.

18. The composition of claim 1, wherein the at least one additive is a hygroscopic agent.

19. The composition of claim 18, wherein the hygroscopic agent is selected from the group consisting of CaO, CaCl2, LiCl, NaCl, CaI2, MgCl2, TiO2, CaCO3, aluminum silicate fillers and SiO2.

20. The composition of claim 1 or 19, wherein the at least one additive is CaO.

21. The composition according to claim 20, further comprising one or more additives selected from inorganic salts.

22. The composition of claim 1, wherein water degradation increases as the amount of the at least one additional bioplastic increases relative to the amount of the at least one cross-linking compound.

23. The composition of claim 1, wherein water degradation is prevented or slowed or delayed as the amount of the at least one additional bioplastic is reduced relative to the amount of the at least one cross-linking compound.

24. A composition according to claim 23, wherein the at least one additional bioplastic is PEO.

25. The composition of claim 1, wherein the at least one cross-linking compound and the at least one additional bioplastic are present in a ratio of about 1:5, respectively.

26. The composition of claim 25, wherein the at least one cross-linking compound is PAA and the ratio is 1:5 PAA:PEO.

27. The composition of claim 1, wherein the at least one cross-linking compound and the at least one additional bioplastic are present in a ratio of 2:8, respectively.

28. The composition of claim 27, wherein the at least one cross-linking compound is PAA and the ratio is 2:8 PAA:PEO.

29. The composition of claim 5, wherein the ratio between the amount of PEO and PAA combined and PVOH is 2:98, respectively.

30. The composition of claim 5, wherein the ratio between PEO and PAA combined with PCL and PVOH is 2:5:93 PEO / PAA:PCL:PVOH.

31. The composition of claim 1, wherein the at least one cross-linking compound is present in an amount between 0.4 wt% and 0.5 wt%.

32. The composition of claim 1, wherein the at least one cross-linking compound is present in an amount between 0.9 wt% and 1.1 wt%.

33. The composition of claim 1, wherein the amount of PVOH is between 80 wt% and 99 wt%; or 78 wt% and 90 wt%.

34. The composition of claim 1, wherein the at least one cross-linking compound is present in an amount between 0.1 wt% and 5 wt%; or 1 wt% and 7 wt%.

35. The composition of claim 1, wherein the at least one bioplastic is present in an amount between 0.1 wt% and 47 wt%; or between 5 wt% and 50 wt%.

36. The composition of claim 1, wherein the at least one additive is present in an amount between 0.1 wt% and 17 wt%; or 1 wt% and 20 wt%.

37. A composition according to claim 1, wherein the PVOH is present in an amount between 91.5wt%-99wt%, 83wt%-98.7wt%, 82wt%-98.6wt% or 78wt%-98.2wt%; and the at least one cross-linking compound is present in an amount between 0.1wt%-1.5wt%, 1wt%-2.5wt%, 1.5wt%-4wt%, 5wt%, or 0.5wt%-2wt%; and / or the at least one bioplastic is present in an amount between 1.5wt%-10wt%, 1wt%-5wt% or 0.1wt%-1wt%, and wherein the composition optionally comprises at least one additive.

38. The composition of claim 5, comprising PVOH, PAA and PEO, respectively, in amounts selected from: 81wt%-90wt%, 1.5wt%-2wt% and 2wt%; 91.5wt%-99wt%, 0.1wt%-0.5wt% and 0.1wt%-1wt%; 87.5wt%-98.7wt%, 0.1wt%-0.5wt% and 1wt%-5wt%; 94.6wt%-82.5wt%, 0.1wt%-0.5wt% and 5wt%-10wt%; 87wt%-93.3wt%, 0.5wt%-2wt% and 0.1wt%-1wt%; 83wt%-98.7wt%, 0.5wt%-2wt% and 1wt%-5wt%; 78.5wt%-94.3wt%, 0.5wt%-2wt% and 5wt%-10wt%; 79.5wt%-93.8wt%, 0.1wt%-0.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%; 81.5wt%-93.7wt%, 0.1wt%-1.5wt% and 0.1wt%-1wt%; and further optionally comprising PCL in an amount ranging between 5wt%-10wt%; or 82wt%-98.6wt%, 1wt%-2wt% and 0.1wt%-1wt%; and further optionally comprising PCL in an amount ranging between 1wt%-5wt%.

39. A process for improving at least one property of a solid composite material formed from a composition according to any one of claims 1 to 38, the process comprising treating a composition comprising an amount of a cross-linking compound and an amount of PEO with a composition comprising an amount of PVOH and optionally at least one additive, wherein: The amount of cross-linking compound, the amount of PEO and optionally the amount of PVOH are selected to improve the at least one property under conditions that allow the cross-linking compound, PEO and PVOH and optionally at least one additive to be compounded into a solid composite having the at least one property, wherein the at least one property is water degradation.

40. The process of claim 39, wherein the cross-linking compound is PAA.

41. The process of claim 40, wherein the amount of PAA and the amount of PEO are in a ratio of about 1:5, respectively.

42. The process of claim 40, wherein the amount of PAA and the amount of PEO are in a ratio of about 2:

8.

43. The process of claim 42, wherein the ratio of PAA:PEO is 2:

8.

44. The process of claim 40, wherein the ratio between the amount of PEO and the amount of PAA combined and the amount of PVOH is 2:98 respectively.

45. The process of claim 40, wherein the ratio between the amount of PEO and the amount of PAA combined to the amount of PCL and the amount of PVOH is 2:5:93 PEO / PAA:PCL:PVOH.

46. ​​The process of claim 40, wherein the amount of PAA is between 0.4 wt% and 0.5 wt%.

47. The process of claim 40, wherein the amount of PAA is between 0.9 wt% and 1.1 wt%.

48. The process of claim 39 or 40, wherein the amount of PVOH is between 80 wt% and 99 wt%; or 78 wt% and 90 wt%.

49. The process of claim 40, wherein the amount of PAA is between 0.1 wt% and 5 wt%; or 1 wt% and 7 wt%.

50. The process of claim 39 or 40, wherein the amount of PEO is between 0.1 wt% and 47 wt%; or 5 wt% and 50 wt%.

51. The process of claim 40, wherein the PVOH is present in an amount between 91.5 wt%-99 wt%, 83 wt%-98.7 wt%, 82 wt%-98.6 wt%, or 78 wt%-98.2 wt%; and the PAA is present in an amount between 0.1 wt%-1.5 wt%, 1 wt%-2.5 wt%, 1.5 wt%-4 wt%, 5 wt%, or 0.5 wt%-2 wt%; and / or the PEO is in an amount between 1.5 wt%-10 wt%, 1 wt%-5 wt%, or 0.1 wt%-1 wt%, and wherein the composition optionally comprises at least one additive.

52. The process of claim 40 comprising PVOH, PAA and PEO, each in an amount selected from: 81wt%-90wt%, 1.5wt%-2wt% and 2wt%; 91.5wt%-99wt%, 0.1wt%-0.5wt% and 0.1wt%-1wt%; 87.5wt%-98.7wt%, 0.1wt%-0.5wt% and 1wt%-5wt%; 94.6wt%-82.5wt%, 0.1wt%-0.5wt% and 5wt%-10wt%; 87wt%-93.3wt%, 0.5wt%-2wt% and 0.1wt%-1wt%; 83wt%-98.7wt%, 0.5wt%-2wt% and 1wt%-5wt%; 78.5wt%-94.3wt%, 0.5wt%-2wt% and 5wt%-10wt%; 79.5wt%-93.8wt%, 0.1wt%-0.5wt% and 5wt%-10wt%; and optionally further comprising PCL in an amount ranging between 1wt%-5wt%; 81.5wt%-93.7wt%, 0.1wt%-1.5wt% and 0.1wt%-1wt%; and further optionally comprising PCL in an amount ranging between 5wt%-10wt%; or 82wt%-98.6wt%, 1wt%-2wt% and 0.1wt%-1wt%; and further optionally comprising PCL in an amount ranging between 1wt%-5wt%.

53. The process of claim 40, wherein adjusting comprises increasing the amount of PEO relative to PAA to increase water degradation.

54. The process of claim 40, wherein adjusting comprises increasing the amount of PAA relative to PEO to reduce water degradation.

55. The process of claim 40, wherein adjusting comprises reducing the amount of PEO relative to PAA to reduce water degradation.

56. The process of claim 40, wherein adjusting comprises decreasing the amount of PAA relative to PEO to increase water degradation.

57. A process for adjusting the water degradation profile of a solid composite material formed from a composition according to any one of claims 1 to 38, the process comprising treating a composition comprising an amount of a cross-linking compound and an amount of PVOH and optionally at least one additive with an effective amount of PEO, the effective amount being selected to increase or decrease water degradation of the solid composite, wherein the process is carried out under conditions that allow the cross-linking compound, PEO and PVOH and optionally at least one additive to be compounded into the solid composite having the water degradation profile.

58. A process for setting the onset of water degradation of a solid composite comprising PVOH, the process comprising: When preparing the water-free composition comprising PVOH, at least one cross-linking compound and at least one additional bioplastic according to any one of claims 1 to 38, the amount of the at least one cross-linking compound and the amount of the at least one additional bioplastic are selected to accelerate or delay the water degradation of the solid composite in combination, and thermally treating the composition to form the solid composite; wherein the cross-linking compound has a functional group capable of associating with PVOH, and the cross-linking compound is selected from dicarboxylic acids, tricarboxylic acids and higher homologous carboxylic acid compounds; and Wherein, the at least one additional bioplastic is a biodegradable polymer, and the at least one additional bioplastic is selected from poly(ethylene oxide) (PEO), poly(ethylene glycol) (PEG), polycaprolactone (PCL), poly(lactic acid) (PLA), cellulose and cellulose derivatives, starch, chitosan and polyhydroxyalkanoates (PHA).

59. A polymer composite formed from the composition of any one of claims 1 to 38.

60. The composite of claim 59, having a molecular weight of ˜1 mg / (min×cm 2 )’s water degradation rate.

61. The composite of claim 59, having a viscosity of 0.2 mg / (min×cm 2 )’s water degradation rate.

62. A composite made according to the process of any one of claims 39 to 58.

63. A composite according to any one of claims 59 to 62, in the form of particles of material.

64. A compound according to any one of claims 59 to 62 in the form of a masterbatch.

65. A composite according to any one of claims 59 to 62, in the form of a 1D object, a 2D object or a 3D object.

66. An object comprising the composite according to any one of claims 59 to 62.

67. The object according to claim 66 is a 1D object, a 2D object or a 3D object.